Determinants of dividend policy: Pre and post impact of financial crisis 2008 / Muhammad Amirul Hakimi Mohd Yusoff - Mohd Yusoff, Muhammad Amirul Hakimi (2017)
The topic of dividend is an evergreen topic where the decision on dividend by corporate is debatable among academicians. Numbers of studies has been conducted and theories emerged from time to time however, there are still a gap of knowledge. The primary research by Black (1976) suggest dividend as a puzzle. Where the ultimate goals of a firm is to maximize the shareholder's wealth, the decision on dividend has been very subjective considering the internal and external factors of a paying firm. This decision also cause the pattern of dividend policy of a firm to change. This paper analyse the determinants of dividend policy in a property developer (construction) firm in Malaysia. By using Pooled Ordinary Least Square (POLS) method, variables such as SIZE, PROFIT, LIQ and LEV will be tested to generate result findings. Global Financial Crisis 2008 also has been taken into consideration towards the study. This study performed an analysis of pre and post-impact of global financial crisis 2008, towards the changes of DPR. Using dummy variable to differentiate the factor, three model has been developed for regressions. The result findings of this study revealed that in every model, variable LEV and SIZE has significant relationships towards DPR. Variables LIQ and PROFIT in every model shows insignificant relationship against DPR. The analysis of pre and post impact of global financial crisis 2008 also revealed to have inconsistent results between pre and post impact. The inconsistent result is in term of the coefficient of variables. However, the dummy variable (global financial crisis) is not significant to the study both pre and post-crisis. This concludes that global financial crisis 2008 has less or no impact towards Malaysia constructions firms in determining dividend payout.